Landscape-scale Conservation Planning - Trombulak, Stephen C.; Baldwin, Robert (Springer Netherlands : Imprint: Springer, 2010)
This book expands the thinking and techniques of the new field of systematic conservation planning to include significant improvements borne of integrating social and natural conditions and processes to address the questions and problems of protecting ecosystem pattern and process in human-dominated landscapes. Specifically it undertakes to answer the question of how to accomplish ecoregion-scale, transboundary conservation in a variety of realms including seascapes, multiple nations and jurisdictions, all by using numerous conservation targets and by incorporating changing climate, land use, and other social and natural processes operating at multi-spatial and temporal scales.